PENGARUH PENDAMPINGAN ORANG TUA TERHADAP KESEHATAN MENTAL SISWA SEKOLAH DASAR DALAM PEMBELAJARAN JARAK JAUH DI SDN PALURAHAN KABUPATEN PANDEGLANG BANTEN - Andri Imam Subekhi; Swastika Oktavia (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2022)
Distance learning conducted online should be the responsibility of parents to accompany their children as a substitute teacher. The purpose of this study was to determine the effect of parental assistance on the mental health of elementary school students in distance learning. The qualitative method was carried out with a case study approach, and with 10 participants, 5th grade students in an elementary school in Pandeglang. The students are 9-10 years old. Sampling was done by purposive sampling and data analysis was done descriptively. In this study, two data collection techniques were used, namely questionnaires and interviews. From the results of the study, it can be concluded that parental assistance has an effect on the mental health of elementary school students in distance learning. However, it was found that there were many factors that hindered parental assistance. One of the main inhibiting factors was the busyness of parents and the readiness of parents as substitute teachers. During distance learning, children feel bored due to monotonous learning and children are more likely to be addicted to cellphones